The Influence Of Tax Planning, Earning Growth, Asset Management, And Good Corporate Governance On Company Value - Arhayu Lik,anatus Sholikah; Sri Andriani (Universitas Muhammadiyah Makassar, 2022)
This study aims to examine the effect of tax planning, earning growth, asset management and good corporate governance on firm value. The sample in this study were companies listed jakarta Islamic Indeks (JII) that have been listed on the Indonesia Stock Exchange (IDX) in 2017-2020, based on the purposive sampling method obtained 17 companies. In this study the data were processed using SPSS with multiple linear regression. The method of testing the hypothesis uses a significance level of 5%. The result showed the tax planning variable is calculated by ETR and BTD has a negative effect on firm value. Earning growth has a positive effect on firm value. Asset management has a positive effect on firm value. Good corporate governance has no effect on firm value.